Cohort profile: prevalence of valvular heart disease in community patients with suspected heart failure in UK - Rajan Sharma; Anna Marciniak; Keli Glover (BMJ Open)
Purpose The aim of this study was to evaluate the proportion of suspected heart failure patients with significant valvular heart disease. Early diagnosis of valve disease is essential as delay can limit treatment and negatively affect prognosis for undiagnosed patients. The prevalence of unsuspected valve disease in the community is uncertain.Participants We prospectively evaluated 79 043 patients, between 2001 and 2011, who were referred to a community open access echocardiography service for suspected heart failure. All patients underwent a standard transthoracic echocardiogram according to British Society of Echocardiography guidelines.Findings to date Of the total number, 29 682 patients (37.5%) were diagnosed with mild valve disease, 8983 patients (11.3%) had moderate valve disease and 2134 (2.7%) had severe valve disease. Of the total number of patients scanned, the prevalence of aortic stenosis, aortic regurgitation, mitral stenosis, mitral regurgitation was 10%, 8.4%, 1%, and 12.5% respectively. 18% had tricuspid regurgitation. 5% had disease involving one or more valves.Conclusions Of patients with suspected heart failure in the primary care setting, a significant proportion have important valvular heart disease. These patients are at high risk of future cardiac events and will require onward referral for further evaluation. We recommend that readily available community echocardiography services should be provided for general practitioners as this will result in early detection of valve disease.